Juridical Analysis Of Fraud Committed By Housing Developers (Study Decision Number: 397/Pid.B/2021/PN Bna) - Adlin; Saiful Asmi Hasibuan (International Journal of Society and Law, 2024)
This study explores the significant challenges posed by property fraud in the rapidly expanding urban property market, focusing on a specific legal case in Indonesia (Case Number: 397/Pid.B/2021/PN-BNA). As urban populations grow and the demand for residential housing increases, the property sector becomes a lucrative but contentious area, leading to various conflicts and crimes, particularly fraud. Property fraud, facilitated by perpetrators exploiting legal ambiguities and weaknesses in law enforcement, causes substantial financial and psychological harm to victims, undermining social trust and stability. The study examines the legal distinction between fraud and default, the role of law enforcement, and the need for comprehensive public education on property regulations. Through the case of Maidin Rahmat Bin Sulaiman, who was sentenced to three years and six months for property fraud, this analysis highlights the intricacies and consequences of fraudulent activities in the housing sector. The findings underscore the necessity for stringent legal measures and effective enforcement to deter property fraud and protect consumers in the real estate market.